MATHEMATICS TEACHER COMPETENCY DEVELOPMENT THROUGH DIFFERENTIATED ALGEBRA LEARNING WEBINAR AND JUNIOR HIGH SCHOOL MATHEMATICS LEARNING WORKSHOP ASSISTED BY GEOGEBRA - Patunah, Siti; Nuralam, Humam; Jupri, Al; Purwanti, Lina Asih; Winardi, Monica Priska Aprilia; Sartika, Rahma Adinda; Khair, Salsabila Nazhifatin; Masitoh, Siti; Nafiah, Siti; Drajat, Widi Rahmawati; Tanjung, Winda Khadijah Ashaerani (Jurnal Abdimas Bina Bangsa, 2025)
The development of technology can transform the learning process, especially in relation to instructional media. Existing instructional media can be modified and developed according to technological advancements and in alignment with the Merdeka Curriculum. Based on a needs survey, 100% of teachers require training in creating instructional media and materials related to differentiated learning, while 40% of teachers express difficulty and the need for training in algebraic concepts. This community service activity aims to enhance mathematics teachers' competence in implementing differentiated learning, particularly in algebra, and using GeoGebra technology in teaching mathematics at the Junior High School level. The activity consists of two parts: webinars and workshops. The webinars focus on the concept and strategies of differentiated algebra-based learning approaches, aimed at helping teachers understand the diverse learning needs of students. Meanwhile, the workshops provide practical training for teachers in using GeoGebra to enrich mathematics education, especially in visualizing algebraic concepts. Through this activity, teachers are expected to apply a more effective and inclusive approach to mathematics education and improve their technology utilization skills in the classroom. Evaluation results showed an 80.7% increase in teachers' understanding of differentiated learning and an 82.7% improvement in teachers' skills in using GeoGebra. Additionally, 84.6% of teachers stated that using GeoGebra in instruction is essential to help students understand algebraic concepts.